The vibrational spectrum of the hydrated alanine-leucine peptide in the amide region from IR experiments and first principles calculations - Hassan, Irtaza; Donati, Luca; Stensitzki, Till; Keller, Bettina G.; Heyne, Karsten; Imhof, Petra (Chemical Physics Letters, 2018)
We have combined infrared (IR) experiments with molecular dynamics (MD) simulations in solution at finite temperature to analyse the vibrational signature of the small floppy peptide Alanine-Leucine. IR spectra computed from first-principles MD simulations exhibit no distinct differences between conformational clusters of α-helix or β-sheet-like folds with different orientations of the bulky leucine side chain. All computed spectra show two prominent bands, in good agreement with the experiment, that are assigned to the stretch vibrations of the carbonyl and carboxyl group, respectively. Variations in band widths and exact maxima are likely due to small fluctuations in the backbone torsion angles.
CRIS-Team Scopus Importer:2020-02-18
Keywords: First-principles molecular dynamics simulations; Infrared spectra; Peptide